Puss in Boots [videorecording (Blu-Ray)] - Wheeler, Thomas (Screenwriter); Miller, Chris, 1975- (Universal Pictures Home Entertainment, 2018)
A story about the events leading up to the sword fighting cat's meeting with Shrek and his friends. Years before meeting Shrek and Donkey, the adorable but tricky Puss in Boots must clear his name from all charges making him a wanted fugitive.